The exile as Sabbath rest : the Chronicler's interpretation of the exile - Jonker, Louis C. (Old Testament essays, 2007)
In 2 Chr 36:20-21 we find an interesting perspective on the length and end of the Exile. It is indicated there that the Exile continued until the establishment of the Persian Kingdom, but also that this happened in fulfilment of the word of Yahweh through his prophet Jeremiah who prophesied that they will serve the king of Babylon 70 years long (cf. Jer 25:11; 29:10). These seventy years are then interpreted by the Chronicler as a period of Sabbath rest for the land (most probably on account of Lev 26:34ff.). This contribution is an attempt to formulate a theory as to why the Chronicler altered his Vorlagen about the Exile so much.